2017
DOI: 10.1038/s41598-017-06783-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a sex pheromone of the chrysanthemum lace bug Corythucha marmorata (Hemiptera: Tingidae)

Abstract: Although the nymphs of Corythucha marmorata form clusters on the undersides of host plant leaves, as frequently observed for Hemiptera, the adults are scattered in the vicinity of the nymph population. By investigating the biological activities of volatile secretions from the adult, we found that the secretions activated male mounting behaviour. A chemical analysis revealed that borneol was a common component of the secretions from both sexes. The absolute configuration of the natural product was the (+)-enant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…others being attractants depending on the dose and insect species in question [62][63][64][65][66]. It is of note that those attracted to the compounds outwardly tend to be herbivorous, and those repelled are blood feeding; given the relative conservation of olfactory stimuli in blood feeding arthropods, it is possible that the blends described herein will have functions beyond mosquito control.…”
Section: Plos Onementioning
confidence: 99%
“…others being attractants depending on the dose and insect species in question [62][63][64][65][66]. It is of note that those attracted to the compounds outwardly tend to be herbivorous, and those repelled are blood feeding; given the relative conservation of olfactory stimuli in blood feeding arthropods, it is possible that the blends described herein will have functions beyond mosquito control.…”
Section: Plos Onementioning
confidence: 99%
“…This compound has been proved to exert anti-inflammatory activity (Tung et al 2008). Interestingly, bornyl acetate is used by some insects, such as Corythucha marmorata (Uhler) (Hemiptera: Tingidae), as a source of sex pheromones (Watanabe and Shimizu 2017). 1-Nonene is a linear alkene occurring in the defensive secretions of tenebrionid beetles (Tschinkel 1975).…”
Section: Chemical Analysis Of Solidago Essential Oilsmentioning
confidence: 99%
“…In this regard, it has been reported that goldenrod is an important source of nectar for honeybees (Stefanic et al 2003). Besides, the fact that some major leaf volatile constituents of S. gigantea and S. canadensis EOs, such as germacrene D and bornyl acetate, are pheromones within species belonging to cockroaches and lacewings (Kitamura et al 1996;Watanabe and Shimizu 2017), should give a low risk from an ecotoxicological standpoint. Notably, Solidago spp.…”
Section: Chemical Analysis Of Solidago Essential Oilsmentioning
confidence: 99%
“…Furthermore, these compounds exhibit various properties such as antibacterial and antifungal activity, inhibition of nematode growth [15], inhibition of prostaglandin H synthase [16], and repellence of birds [17]. Chemical ecology research on the family Tingidae has focused on two invasive species of the genus Corythucha (C. ciliate (Say) and C. marmorata (Uhler)), leading to the identification of alarm pheromones [18,19] and sex pheromone [20].…”
Section: Introductionmentioning
confidence: 99%